Microwave-Assisted Synthesis of 2-Aryl-2-oxazolines, 5,6-Dihydro-4H-1,3-oxazines, and 4,5,6,7-Tetrahydro-1,3-oxazepines - Mollo, María Cruz (2016)
The first general procedure for the synthesis of 5- to 7-membered cyclic iminoethers by microwave-assisted cyclization of ω-amido alcohols promoted by polyphosphoric acid (PPA) esters is presented. 2-Aryl-2-oxazolines and 5,6-dihydro-4H-1,3-oxazines were efficiently prepared using ethyl polyphosphate/CHCl3. Trimethylsilyl polyphosphate in solvent-free conditions allowed for the synthesis of hitherto-unreported 4,5,6,7-tetrahydro-1,3-oxazepines. The method involves good to excellent yields and short reaction times.The reaction mechanism and the role of PPA esters were investigated in a chiral substrate.